THE EFFECT OF DIFFERENT CONCENTRATIONS OF ADDING TALIPUK FLOUR (Nymphae pubescens WILLD) ON THE PHYSICAL AND CHEMICAL PROPERTIES OF RICE VERMICELLI PRODUCTS - Azkiyyah, Siti Raihana; Yulinda, Ratna; Putri, Rizky Febriyani; Istyadji, Maya (Transpublika Publisher, 2023)
The high usage of rice in food products has led to a scarcity of national rice supply, which underpins this research. Talipuk is a seed from the water lily species Nymphae pubescens WILLD, abundantly available in the swamps of South Kalimantan. The addition of talipuk flour in vermicelli production is expected to reduce the reliance on rice flour. This study aims to investigate the influence of talipuk flour addition on the physical and chemical properties of vermicelli. The research adopts an experimental approach with a quantitative method, utilizing a completely randomized design by combining varying levels of rice flour and talipuk flour. Data analysis employs one-way ANOVA to determine significant differences among treatments. The results indicate that different treatments significantly affect the physical properties of vermicelli, including water absorption, integrity, and durability. Treatment variations influence chemical properties such as crude protein content and crude fiber but do not affect moisture content, ash content, and carbohydrate content.